(untitled) (NEW: Emerging scholars in Australian Indigenous Studies, 2020)
In an election campaign that spent much time around esoteric ideas like dividend imputation credits and electric vehicle targets, it is strange that little time was spent discussing Labor’s proposal to enshrine a Voice to Parliament for First Nations people in the constitution, via referendum. Unlike nations such as New Zealand or Norway, Australia lacks a specified mechanism for First Peoples’ political representation. As with our decades of inaction on constitutional recognition of Australia’s Indigenous peoples, this can also be seen manifesting in our inability to improve educational, health, and justice outcomes for Indigenous Australia. Individuals like newly appointed Minister for Indigenous Affairs, Ken Wyatt, and Member for Barton, Linda Burney, can and do break through this glass ceiling. But such examples serve as outliers rather than the norm, as Indigenous Land Rights leader Galarrwuy Yunipingu noted, ‘I have had a place at the table of the best and the brightest in the Australian nation - and at times success has seemed so close, yet it always slips away’ (Yunipingu 2008, para. 20). The Uluru Statement from the Heart sought to show a path forward from the ‘torment of our powerlessness’ and for ‘reforms to empower our people and take a rightful place in our own country’.